AI TECHNOLOGIES TO THE QUESTION OF THE "POLICY" OF LEGAL REGULATION AT THE PRESENT STAGE. ESSENTIAL AND INSTRUMENTAL FACTORS - Nataliya Onishchenko,; Oleksii Kostenko,; Dmytro Zhuravlov, (International Journal of Innovative Technologies in Social Science, 2025)
The article examines the essential characteristics of rulemaking activity in the context of modern challenges and priorities, which is analyzed with due regard for the instrumental and essential typologizing elements. It is noted that one of the priority areas for the development of rulemaking at the present stage is to consider the “achievements” of the latest technologies related to artificial intelligence. It is emphasized that rulemaking at all levels should ensure human rights and freedoms (in particular, this refers to the improvement of veteran policy at the present stage, its forms, and methods).